Outcomes of multimodal therapy in a large series of patients with anaplastic thyroid cancer. Issue 2 (8th October 2019) - Fan, Dan; Ma, Jennifer; Bell, Andrew C.; Groen, Andries H.; Olsen, Kyrie S.; Lok, Benjamin H.; Leeman, Jonathan E.; Anderson, Erik; Riaz, Nadeem; McBride, Sean; Ganly, Ian; Shaha, Ashok R.; et al.
Abstract : Background: The role of radiotherapy (RT) in the treatment of patients with anaplastic thyroid cancer (ATC) for local tumor control is critical because mortality often is secondary to complications of tumor volume rather than metastatic disease. Herein, the authors report the long‐term outcomes of RT for patients with ATC. Methods: A total of 104 patients with histologically confirmed ATC were identified who presented to the study institution between 1984 and 2017 and who received curative‐intent or postoperative RT. Locoregional progression‐free survival (LPFS), overall survival (OS), and distant metastasis–free survival were assessed. Results: The median age of the patients was 63.5 years. The median follow‐up was 5.9 months (interquartile range, 2.7‐17.0 months) for the entire cohort and 10.6 months (interquartile range, 5.3‐40.0 months) for surviving patients. Thirty‐one patients (29.8%) had metastatic disease prior to the initiation of RT. Concurrent chemoradiation was administered in 99 patients (95.2%) and 53 patients (51.0%) received trimodal therapy. Systemic therapy included doxorubicin (73.7%), paclitaxel with or without pazopanib (24.3%), and other systemic agents (2.0%). The 1‐year OS and LPFS rates were 34.4% and 74.4%, respectively. On multivariate analysis, RT ≥60 Gy was associated with improved LPFS (hazard ratio [HR], 0.135; P  = .001) and improved OS (HR, 0.487; P  = .004), and trimodal therapy was associated with improved LPFS (HR, 0.060; P  = .017). The most commonly observed acute grade 3 adverse events included dermatitis (20%) and mucositis (13%), with no grade 4 subacute or late adverse events noted (adverse events were graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events [version 4.0]). Conclusions: RT appears to demonstrate a dose‐dependent, persistent LPFS and OS benefit in patients with locally advanced ATC with an acceptable toxicity profile. Aggressive RT should be strongly considered for the treatment of patients with ATC as part of a trimodal treatment approach. Abstract : Radiotherapy demonstrates a dose‐dependent, persistent locoregional progression‐free survival and overall survival benefit in patients with locally advanced anaplastic thyroid cancer (ATC) with an acceptable toxicity profile. Aggressive radiotherapy should be strongly considered in the treatment of ATC as part of a trimodal treatment approach.